2013
DOI: 10.1016/j.jhazmat.2012.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationship between heavy metals in road-deposited sediments and washoff particles in urban stormwater using simulated rainfall

Abstract: h i g h l i g h t sHeavy metal concentrations in washoff particles increased by 10-30% compared with RDS. Rainfall intensity and duration did not affect increased rate of metal concentrations. Grain size of RDS and washoff particles carrying most heavy metals was different. Metal concentrations in RDS washoff decreased along the urban-rural gradient. Understanding the relationship between heavy metals in road-deposited sediments (RDS) and washoff particles is essential to controlling urban runoff pollution. RD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(30 citation statements)
references
References 36 publications
0
26
0
4
Order By: Relevance
“…In past studies, Zhao and Li [6] reported that rainfall intensity and duration affected pollutants in the wash-off process, but did not affect particle size composition in washed-off pollutants. Lee et al [7] analyzed hydrographs and pollutographs, indicating that transportation for most of the pollutants depended on the preceding dry period and rainfall intensity.…”
Section: Introductionmentioning
confidence: 97%
“…In past studies, Zhao and Li [6] reported that rainfall intensity and duration affected pollutants in the wash-off process, but did not affect particle size composition in washed-off pollutants. Lee et al [7] analyzed hydrographs and pollutographs, indicating that transportation for most of the pollutants depended on the preceding dry period and rainfall intensity.…”
Section: Introductionmentioning
confidence: 97%
“…Notably, the current knowledge about the pollutant wash-off process does not extend to a clear understanding about the variability (load and composition) associated with the process (Egodawatta and Goonetilleke, 2008;Hossain et al, 2011;Vaze and Chiew, 2003;Zhao and Li, 2013). Consequently, significant issues emerge in relation to the formulation of robust strategies for the mitigation of urban water pollution as poor characterisation of process variability in urban …”
Section: Introductionmentioning
confidence: 99%
“…The series of units UCA, CSA, RTA, RVA and UVA has the urban-rural gradient feature with gradient variation of several important characteristics of different administrative divisions, such as population density, average daily traffic, total energy consumption, street cleaning method and frequency. In general, population density, traffic density, energy consumption, and frequency of sweeping decreased along the urban-rural gradient, as shown in Table 1 (Zhao and Li, 2013). Additionally, UCA and CSA have relatively smooth and less damaged impervious surfaces, and regularly daily mechanical sweeping; RTA, RVA and UVA have heavily damaged imperious surfaces, and rarely street sweeping.…”
Section: Study Area and Road Dust Samplingmentioning
confidence: 95%